The influence of Ferrous Sulphate @ 300 mg ingestion shortly after meal and 2 hours after meal on pharmacokinetic profiles of iron in serum sample in women with Hb 2 12 g/dL - Erna Kristin, Erna Kristin (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Iron absorption is determined by iron status, heme- and nonheme-iron contents and amounts of various dietary factors that influence iron absorption. Few studies have examined the influence of food to iron absorption but only limited information is available about the net effect of these factors.Objectives: Objective of this study was to know the influence of Ferrous Sulphate @ 300 mg ingestion shortly after and 2 hours after meal on pharmacokinetic profiles of iron in serum sample in 12 women with Hb >_ 12 g/dLMethods: The study was carried out in a cross over design in which each of participants underwent 2pharmacokinetic studies. One tablet of Ferrous Sulphate @ 300 mg was taken by each subject shortly after and 2 hours after standard meal at the first and second study. Series of serum samples were taken at0, 0.25, 0.5, 1, 1.5, 2, 2.5, 3, 4, 6, 8, 10, and 12 hours after iron administration. The concentrations of ferric iron in serum were measured using Vitors Fe Slides System, while pharmacokinetics parameters were calculated using a non-compartmental method.Results: Pharmacokinetic parameters obtained from the first and second study were compared using t test with the following results (meant SEM): C,,, 275.92 ± 28.97 & 284.58 ± 30.44 ug/dL, T.3.50 ± 0.29& 3.50 ± 0.38 hours, K. 0.3235 t 0.0011 & 0.3816 ± 0.0010 hours-, Ka, 0.1138 ± 1.5696 & 0.1152 ±1.3331 hours T,201 7.80 ± 1.45 & 7.03 ± 1.02 hours and AUCo-12 2493.43 ± 397.54 & 2331.15 ± 283.64 ug/dL.hours. No difference of all pharmacokinetic parameters were detected by intervention typeConclusions: It can be concluded that after ingestion of Ferrous Sulphate @ 300 mg in women with Hb 12 ug/dL shortly after and 2 hours after meal did not show significant diferrences on pharmacokinetic profiles of iron in serum sampleKey words: iron absorption - pharmacokinetic - ferrous sulphate - absorption rate - Cmax